The Advent of COVID-19; Periodontal Research Has Identified Therapeutic Targets for Severe Respiratory Disease; an Example of Parallel Biomedical Research Agendas - Cardoso, Elaine O. C.; Fine, Noah; Glogauer, Michael; Johnson, Francis; Goldberg, Michael; Golub, Lorne M.; Tenenbaum, Howard C. (Frontiers in Dental Medicine, 2021)
The pathophysiology of SARS-CoV-2 infection is characterized by rapid virus replication and aggressive inflammatory responses that can lead to acute respiratory distress syndrome (ARDS) only a few days after the onset of symptoms. It is suspected that a dysfunctional immune response is the main cause of SARS-CoV-2 infection-induced lung destruction and mortality due to massive infiltration of hyperfunctional neutrophils in these organs. Similarly, neutrophils are recruited constantly to the oral cavity to combat microorganisms in the dental biofilm and hyperfunctional neutrophil phenotypes cause destruction of periodontal tissues when periodontitis develops. Both disease models arise because of elevated host defences against invading organisms, while concurrently causing host damage/disease when the immune cells become hyperfunctional. This represents a clear nexus between periodontal and medical research. As researchers begin to understand the link between oral and systemic diseases and their potential synergistic impact on general health, we argue that translational research from studies in periodontology must be recognized as an important source of information that might lead to different therapeutic options which can be effective for the management of both oral and non-oral diseases. In this article we connect concepts from periodontal research on oral inflammation while exploring host modulation therapy used for periodontitis as a potential strategy for the prevention of ARDS a deadly outcome of COVID-19. We suggest that host modulation therapy, although developed initially for management of periodontitis, and which inhibits proteases, cytokines, and the oxidative stress that underlie ARDS, will provide an effective and safe treatment for COVID-19.